Leg Length Discrepancy and Nonspecific Low Back Pain: 3-D Stereophotogrammetric Quantitative Posture Evaluation Confirms Positive Effects of Customized Heel-Lift Orthotics - Moreno D’Amico; Moreno D’Amico; Edyta Kinel; Piero Roncoletta (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The literature reports evidence of leg length discrepancy (LLD) associated with musculoskeletal disorders, alterations in spinopelvic alignment, and body posture, leading to low back pain and lumbar scoliosis. The most common conservative treatment for LLD is the use of internal or external shoe lifts although no treatment guidelines have been established.Aim: The study aimed to contribute to low back pain–LLD relationship comprehension, highlighting the benefits of LLD correction in the nonspecific low back pain (NSLBP) population.Methods: A cross-sectional observational study recruited a cohort of 80 NSLBP patients (48 females, 32 males) with LLD, age (μ = 35 ± 17.2). Entire body posture, including 3-D spine shape reconstruction, was measured using a nonionizing 3-D optoelectronic stereophotogrammetric approach. After the first 3-D posture evaluation, patients were provided with customized orthotics, including 100% LLD heel lift correction. No other therapeutic interventions were considered. Pain level was assessed using the numerical pain rating scale (NPRS). The gender, age-related, and time-dependent effects of LLD equalization treatment in NSLBP patients was investigated during 2 years of follow-up. The statistical analysis was performed at the global level using multivariate methods by Hotelling T2 tests and intrasubject-level using t-test.Results and Discussion: An initial average NPRS = 7.8 was determined. In the medium-term follow-up group (4 months), the NPRS dramatically decreased (NPRS = 1.1). The pain disappeared in the long-term (2 years) follow-up group (NPRS = 0). The study results highlight that LLD equalization treatment led to clear statistically significant improvements in all the postural parameters of the frontal plane, including the underfoot load asymmetry. No worsening has been detected. An adaptation period long enough is needed to obtain progressive pain relief improvements and structural posture changes. Younger NSLBP patients showed slightly better improvements than older ones. Minimal differences between healthy young adults’ and NSLBP patients’ postures were found either in natural erect standing posture or when LLD equalization is applied.Conclusion: Heel-lift customized orthotics with 100% LLD correction are an effective short- and long-term treatment in patients with nonspecific LBP, inducing pain symptom recession and stimulating the improvement of postural parameters without contraindications.